Kamus Bali-Indonesia Bidang Istilah Bahasa dan Sastra Bali - Bayu Anantawijaya Nala, Made (Humanis; Vol 20 No 1 (2017), 2017)
The study of "Bali-Indonesia Dictionary of Language and Literature of Bali" aims to know the form and treasury of the term contained in Balinese language and literature. The theory used in the study of this dictionary is Structural Linguistic theory developed by Ferdinand de Saussure and supported by the theory of lexicology and lexicography. At the stage of data collection, the method used is the method of interviews and simak methods assisted with supporting techniques of recording techniques and techniques of record. Furthermore, at the stage of data analysis, using the translational method followed by the basic technique of separating the decisive element with the advanced technique of the appeal technique equates the principal. In this research also used the method of agih with basic technique that is for direct element and technique of sisip. In the presentation of data analysis results used formal and informal methods and their techniques are inductive and deductive thinking techniques. The results of this study are the terms in the form of a basic word consisting of: one syllable basement, the syllable base word, the third syllable word, the fourth syllable word, the five syllable base, the syllable six syllable, the syllable basic word . There is also a derivative word consisting of: the berrixed word, that is, the prefix N-, {m?-}, {p?N-}, suffix {-an}, word confix {p? - / an}, rephrase, and word compound. The term in the form of a phrase that is: endosentric phrase berinduk one consisting of: nominal phrase. Clause-shaped terms are: active clauses. In this study managed to collect terms as many as four hundred and five. Categorically, the most common word class is the noun word class.